The relationship between the indicators of physical preparation and the scores attained in competitions by the junior female gymnasts - Forminte, V. N.; Micu, R.; Potop, V.; Grosu, E. F. (Journal of Physical Education and Sport, 2021)
This paper examines the relationship between the indicators of physical preparation and the scores attained in competition by the junior female gymnasts aged 13-15 years. Materials and methods. 6 junior gymnasts of 13- 15 years old, selected from the national team of Deva, participated in this study. The physical training was assessed by 10 fitness tests. The competition results were recorded in three national competitions (C1-3). The statistical analysis used the following descriptive parameters: mean, standard deviation, nonparametric tests, namely: Z - Wilcoxon Signed Rank Test for Paired Data, Chi-Square Kruskal-Wallis test and R - nonparametric correlation coefficient - Spearman. Results. The assessment of the junior female gymnasts` physical training highlights an increased segmental strength of the arms, abdomen, scapular belt and legs (spring). There were also noticed higher specific endurance and better balance sense. The results obtained in competitions reveal the following elements: in handspring vaults event, they present an increase by 0.27 points in C3, p > 0.05; on uneven bars, the final score (FS) increases by 3.19 points in C3, p < 0.05; on balance beam, the FS is higher by 0.10 points in C3, p > 0.05; on the floor, the FS increases by 0.25 points in C3, p > 0.05. The correlative results analysis between indicators of physical preparation and the results obtained in competitions shows strong and very strong connections in the intervals (R = .60-.79; R = .80-1.0) on each apparatus in C1 and C3. Conclusions. The correlative analysis of the relationship of physical preparation means and the scores attained in competition by junior female gymnasts highlights strong connections between indicators.